“I am a Black man in Canada! I wish I could say differently!”: exploring the impact of direct and indirect encounters with the police and welfare system on anxiety and depression among Black youth in Toronto, Canada - Agbe, Eyram Adzo; Kwarteng, Ann; Tetteh, Tricia; Regragui, Salwa; Williams, Ken; Dlamini, Nombuso; Boateng, Godfred O. (Frontiers in Public Health, 2025)
IntroductionRecent studies point to differences in mental health outcomes among Black youth living in Canada, influenced by structural experiences of anti-Black racism. The influence of policing and encounters with the criminal justice and child welfare systems in Canada on Black youth mental health outcomes remains understudied, exacerbated by the minimal collection of race-based health data in the country.MethodsBased on an intersectional approach and using semi-structured interviews with twenty-four Black youth in the Greater Toronto Area, this study explores how direct and indirect encounters with the criminal justice and child welfare systems in Toronto influence anxiety and depression symptomatology among Black youth and their families.ResultsWe found that this population experienced significant psychosocial weathering and hypervigilance and physical insecurity, with adaptive capacity being eroded by a sense of disposability.DiscussionThis study contributes new evidence to research on criminalization and racism in Canada and proposes a critical health approach to studying these issues by paying attention to the caregiving burden among Black families experiencing criminalization, as well as the influence of space and place in mitigating the health impact of police and welfare encounters.